2021
DOI: 10.3389/fmolb.2021.737039
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Lipidomic Markers Differentiate COVID-19 From Non-Hospitalized and Other Intensive Care Patients

Abstract: Coronavirus disease 2019 (COVID-19) is a viral infection affecting multiple organ systems of great significance for metabolic processes. Thus, there is increasing interest in metabolic and lipoprotein signatures of the disease, and early analyses have demonstrated a metabolic pattern typical for atherosclerotic and hepatic damage in COVID-19 patients. However, it remains unclear whether this is specific for COVID-19 and whether the observed signature is caused by the disease or rather represents an underlying … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 37 publications
4
29
0
Order By: Relevance
“…Several metabolomic studies have indicated that COVID-19 is associated with abnormalities in the concentration of metabolites and lipoproteins in plasma or serum [ 6 20 ]. These findings suggest the reprogramming of some metabolic pathways alongside the reprogramming of the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Several metabolomic studies have indicated that COVID-19 is associated with abnormalities in the concentration of metabolites and lipoproteins in plasma or serum [ 6 20 ]. These findings suggest the reprogramming of some metabolic pathways alongside the reprogramming of the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…[139][140][141] Vascular impairment and thromboembolisms add to the disease's reported multisystem destruction and increased mortality. 142 Schmelter et al 141…”
Section: F I G U R E 2 Immunometabolic Reactions During Coronavirus D...mentioning
confidence: 99%
“…Furthermore, COVID‐19 individuals have neurological symptoms and renal and hepatic impairment 139‐141 . Vascular impairment and thromboembolisms add to the disease's reported multisystem destruction and increased mortality 142 . Schmelter et al 141 used an experiment to evaluate the metabolic and lipoprotein profiling of hospitalized COVID‐19 cases to many healthy controls and a group of cardiogenic shock cases receiving in the same intensive care unit (ICU) who tested negative for COVID‐19.…”
Section: Metabolic Reprogramming During Covid‐19mentioning
confidence: 99%
“…Examination of COVID-19 at the beginning of sickness and through to the progress of the infection differs from asymptomatic to acute pneumonia with severe respiratory distress syndrome, with the most usual symptoms being cough, shortness of breath, diarrhea, fever and tiredness [ 3 , 4 ]. Moreover, contaminated individuals by this RNA virus presented venous thromboembolic incidents linked to endothelial damage and hypercoagulability, immoderate inflammatory status with cytokine storm, immune dysregulation, cholesterol metabolism abnormalities, oxidative stress, hypertension and new onset diabetes [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%